2019
DOI: 10.1038/s41467-019-12298-z
|View full text |Cite
|
Sign up to set email alerts
|

High-fat diet fuels prostate cancer progression by rewiring the metabolome and amplifying the MYC program

Abstract: Systemic metabolic alterations associated with increased consumption of saturated fat and obesity are linked with increased risk of prostate cancer progression and mortality, but the molecular underpinnings of this association are poorly understood. Here, we demonstrate in a murine prostate cancer model, that high-fat diet (HFD) enhances the MYC transcriptional program through metabolic alterations that favour histone H4K20 hypomethylation at the promoter regions of MYC regulated genes, leading to increased ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
128
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(146 citation statements)
references
References 81 publications
6
128
0
2
Order By: Relevance
“…Epidemiological studies show that although high intake of saturated fatty acids (abundant in meat and butter) decrease the survival rate of PCa patients, unsaturated fatty acids (abundant in fish and vegetable oils) reportedly reduce the risk of PCa [35,36]. An animal study showed that mimicking MYC overexpression induces PCa progression in PCa-model mice fed a diet high in saturated fatty acids [37]. However, suppression of PCa cell proliferation by intake of unsaturated fatty acids, such as eicosapentaenoic acids, docosahexaenoic acids, and α-linolenic acids, was demonstrated in an animal study and several in vitro experiments using human PCa cell lines [38][39][40][41].…”
Section: Fatmentioning
confidence: 99%
“…Epidemiological studies show that although high intake of saturated fatty acids (abundant in meat and butter) decrease the survival rate of PCa patients, unsaturated fatty acids (abundant in fish and vegetable oils) reportedly reduce the risk of PCa [35,36]. An animal study showed that mimicking MYC overexpression induces PCa progression in PCa-model mice fed a diet high in saturated fatty acids [37]. However, suppression of PCa cell proliferation by intake of unsaturated fatty acids, such as eicosapentaenoic acids, docosahexaenoic acids, and α-linolenic acids, was demonstrated in an animal study and several in vitro experiments using human PCa cell lines [38][39][40][41].…”
Section: Fatmentioning
confidence: 99%
“…Indeed, recent studies using human prostate regeneration models have shown a carcinogenic effect of steroids [32]. Thus, a diet rich in fat, compatible with a diet high in processed foods, could perhaps contribute to the pathogenesis of prostate cancer [33].…”
Section: Potential Mechanismsmentioning
confidence: 99%
“…It is important to highlight that a recent projection points to Brazil as the next putative global pandemic epicenter for COVID-19, 72 and in September of 2020, Brazil became the country with the second most confirmed cases, equal to 4 123 000. 73 Fortunately, Brazil has the biggest NMR facility in Latin America, the National Center of Nuclear Magnetic Resonance, which houses several field magnets, including 400, 500, 600, 700, and 800 MHz magnets as well as the recently installed 900 MHz magnet (the strongest NMR field magnet in Latin America).…”
Section: Perspective For Brazilmentioning
confidence: 99%